Tri Hita Karana for environmental resilience: Enhancing coral reef conservation and sustainable practices in Mengiat Beach Bali - Tjokorda Gde Agung Wijaya Kesuma Suryawan; Cokorda Istri Agung Vera Nindia Putri; Made Ayu Desy Geriadi; Anak Agung Istri Dwijayanthi; Riyana Miranti (Journal of Community Service and Empowerment, 2024)
This collaborative international community service initiative applies the Tri Hita Karana philosophy to improve coral reef conservation at Bali''s Mengiat Beach. The collaboration between Universitas Ngurah Rai and the University of Canberra integrates traditional wisdom and innovative methods, promoting resilience, sustainable practices, and economic growth while adhering to Tri Hita Karana''s holistic principles. The initiative program combines Marine Protected Areas (MPAs) and the Mars Assisted Restoration System (MARRS) to safeguard coral ecosystems. Participatory Action Research (PAR) empowers communities, aligning with the holistic principles of Tri Hita Karana. The methodology encompasses preparation, education, hands-on training, beach clean-ups, and continuous evaluation, reinforcing coral preservation while promoting sustainable practices and ecological well-being. These strategies align with the Tri Hita Karana philosophy, promoting local engagement and resource management. The donation of Reef Stars by the universities to the Bali Coastal and Marine Biodiversity Foundation reflects a commitment to environmental well-being and long-term harmony. The Mengiat Beach collaboration by two universities and the Bali Coastal and Marine Biodiversity Foundation integrates traditional wisdom and modern methods within the Tri Hita Karana philosophy. Through education, training, and reef restoration, the initiative emphasizes community engagement and ecological resilience.